(untitled) (Damascus University Journal of arts and humanities sciences, 2025)
The research aims to monitor the idea of ​​consolation - philosophy - reviewing the opinions of philosophers who They came Consolation throughout human history. The research attempted to define philosophical consolation and the necessity of this consolation in the face of grief, death and calamities. The aim of the research is to address the problematic question of why consolation, what is consolation? And is philosophy. Able to offer comfort in difficult situations? The research seeks to monitor the idea of ​​philosophical consolation and its relationship to love and sadness. The research attempted to shed light on the relationship between philosophical consolation and death. Philosophical consolation is an urgent need now in a time of moral and ethical decline. Consolation is an invitation to sincere contemplation of adversity, which leads to concern for others. And in the world, and here lies the moral responsibility Consolation calls for sincere contemplation of adversity, and this leads to concern for others and the world and not to self-indulgence, and here lies the moral responsibility. The research confirms that there is no complete cure for the human condition, but lies in providing some helpful tools, including the moral philosophy of consolation.